Diagnosis and treatment of elements affected by molar incisor hypomineralization: a clinical case report (Research, Society and Development, 2022)
Molar Incisor Hypomineralization (MIH) is characterized as a defect in enamel development. Elements that have this systemic alteration clinically present with demarcated white, yellow or brownish opacities. Its etiology remains inconclusive and its cause is considered multifactorial, making it a challenge in pediatric dentistry offices. The article aims to report a clinical case of severe HMI (molar incisor hypomineralization) in an 8-year-old child. For its development, an exploratory search was carried out on Google academic, Pubmed, Scielo of the last ten years and a specific book on the exposed topic. Patient J.L.S.L male, attended the UNITPAC children's clinic with the mother's main complaint 'my son's teeth are very yellow' and difficulty brushing due to tooth sensitivity. Clinically, marked opacities were observed in the dental enamel, with a color ranging from white to yellowish tones, characteristics of HMI, on the buccal surfaces of the maxillary incisors and molars, and on the occlusal surfaces of the 1st mandibular molars with loss of tooth structure. No element showed fistula or any other characteristic sign of pulp involvement. The child was then diagnosed with severe HMI and the proposed treatment required multiple sessions of topical application of varnish, ART restoration in the elements with cavity and use of resin sealant, followed up for 6 months. All in all, we can conclude with the importance of a detailed anamnesis so that there is an early diagnosis, considering the most conservative treatments possible and improving the sensitivity framework.